The Study of The Architectural Characteristics of ‘Umah of The Sakai Tribe in Sumatra - Muhammar Khamdevi; Yantri Komala Dewi (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2021)
The Sakai Tribe or Oghang Daghek (Orang Darat) live simply and depend on nature in the forest and on the banks of rivers. This tribe is one of the tribes in the Central Sumatra region that has ties to the Minangkabau Tribe. The traditional house itself is very simple, which has the characteristics of an early vernacular house in Sumatra. However, a clear and scientific study of the architectural characteristics of this house is still incomplete. What are the characteristics of the Sakai Tribe House? This research was conducted using a qualitative method approach to analyze the object of the case directly in the field descriptively. The purpose of this study is to find the characteristics of this tribal traditional house. This research resulted in the architectural characteristics of the Sakai Tribe.